Lithofacies classification and origin of the Eocene lacustrine fine-grained sedimentary rocks in the Jiyang Depression, Bohai Bay Basin, Eastern China. (1st June 2020) - Shi, Juye; Jin, Zhijun; Liu, Quanyou; Huang, Zhenkai
Graphical abstract: Highlights: Lacustrine shale has strong heterogeneity in terms of its mineral composition. Seven types of lithofacies developed in the Jiyang Depression. Three types of lithofacies assemblages are present in the study area. The Type C lithofacies assemblage is the most favorable exploration target. Abstract: There are multiple sets of lacustrine source rocks in the Paleogene of the Jiyang Depression, Bohai Bay Basin, Eastern China, which are main targets in the terrestrial shale oil exploration. Compared with marine shales, lacustrine fine-grained rocks are more complex in their mineralogical compositions, sedimentary structures and vertical stacking patterns. Therefore, it is of great theoretical and practical significance to carry out petrological characterization and lithofacies classification in lacustrine fine-grained rocks. Based on observations in cores and thin sections as well as elemental and organic geochemical analyses, this study systematically analyzes petrological characteristics of Eocene lacustrine fine-grained sedimentary rocks in the Jiyang Depression from perspectives of mineralogical compositions, sedimentary structures and organic matter abundance. Three end members (carbonate minerals, clay minerals and terrigenous clastic minerals), together with organic matter abundance and sedimentary structure, are employed to establish a lithofacies classification scheme that is suitable for fine-grained rocks in the Jiyang Depression, Eastern China. A total of 7 lithofacies types are recognized, such as the organic matter-rich laminated calcareous mudstone lithofacies and the moderately organic matter-rich layered calcareous mudstone lithofacies. Through analysis of lithofacies from the bottom to the top of the drilling well, sixth-order sequence units are found to have good correspondence to lithofacies assemblages. Based on consideration of magnetic susceptibility, mineral content, and geochemical proxies, these sixth-order sequence units are divided into three types of lithofacies assemblages, namely the Type A lithofacies assemblage corresponding to the dominantly rising base level, Type B lithofacies assemblage corresponding to the dominantly falling base level, and Type C lithofacies assemblage with the isostatic base level. Among them, the Type C lithofacies assemblage is the most favorable for shale oil exploration and development. Results of this study are expected to not only deepen understanding of lithofacies and its genesis and origin of lacustrine fine-grained rocks, but also provide a theoretical basis for shale oil exploration and development.